Airborne copper exposure in school environments associated with poorer motor performance and altered basal ganglia. Issue 6 (22nd April 2016) - Pujol, Jesus; Fenoll, Raquel; Macià, Dídac; Martínez‐Vilavella, Gerard; Alvarez‐Pedrerol, Mar; Rivas, Ioar; Forns, Joan; Deus, Joan; Blanco‐Hinojo, Laura; Querol, Xavier; Sunyer, Jordi
Abstract: Introduction: Children are more vulnerable to the effects of environmental elements. A variety of air pollutants are among the identified factors causing neural damage at toxic concentrations. It is not obvious, however, to what extent the tolerated high levels of air pollutants are able to alter brain development. We have specifically investigated the neurotoxic effects of airborne copper exposure in school environments. Methods: Speed and consistency of motor response were assessed in 2836 children aged from 8 to 12 years. Anatomical MRI, diffusion tensor imaging, and functional MRI were used to directly test the brain repercussions in a subgroup of 263 children. Results: Higher copper exposure was associated with poorer motor performance and altered structure of the basal ganglia. Specifically, the architecture of the caudate nucleus region was less complete in terms of both tissue composition and neural track water diffusion. Functional MRI consistently showed a reciprocal connectivity reduction between the caudate nucleus and the frontal cortex. Conclusions: The results establish an association between environmental copper exposure in children and alterations of basal ganglia structure and function. Abstract : School children are vulnerable to copper levels common in urban environments. Copper appears to interfere with the development of frontobasal ganglia circuits. Copper contribution to neurodegenerative disorders may start early in life.